KEPUASAN PENGGUNA PADA APLIKASI ISUMBAR MAMBACO DI DINAS KEARSIPAN DAN PERPUSTAAKAAN PROVINSI SUMATERA BARATMENGGUNAKAN MODEL E-SERVQUAL - Muhammad Alfarez; Elva Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study measures user satisfaction with the iSumbar Mambaco application at the Regional Archives and Library Office of West Sumatra Province using the E-SERVQUAL model, which includes Efficiency, System Availability, Fulfillment, and Privacy. Employing a quantitative descriptive method through a survey of 88 active users, the data were analyzed using SPSS. The results show that user satisfaction falls into the fairly satisfied to very satisfied category, with the highest score on System Availability (3.26) and the lowest on Privacy (3.10). The application is considered stable and easy to access, though improvements are needed in digital collection and privacy policies. These findings serve as a basis for enhancing digital library services to be more efficient, secure, and user-oriented.